SOCIAL INFLUENCES ON THE SECOND-GENERATION CHINESE AMERICAN’S IDENTITY DEVELOPMENT DEPICTED IN AMY TAN’S THE JOY LUCK CLUB NOVEL - NURLAILY, ALFARATNA SEPTI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: chinese immigrant family, mothers-daughters relationship, individual psychology, generational gap, The Joy Luck Club Chinese immigration to America has taken place since a long time ago because of the World War II. Chinese immigrants bring their new hopes in getting the better lives in America. Unfortunately, not all of the Chinese immigrants can get better lives because they have to face the different culture, language, society, and lifestyle. Those differences later on cause the gap between mothers as the first generation and daughters as the second generation of Chinese immigrant. The novel entitled The Joy Luck Club points out the generational gap through the characters’ individual psychology.The research employs psychological approach in order to reveal more informations focusing on the subject being studied. This approach directs the discussion to use psychology theory to analyze and interpret the data. In this case, the psychology theories are focused on the generational gap which appears because of the different perspectives of mothers and daughters in the Chinese immigrant families.The study reveals that there are different perspectives from mothers as the first-generation Chinese immigrants who still have the Chinese thought and the daughters as the second-generation Chinese immigrants who have already been influenced by the American culture because of the society around them and from their psychological condition in shaping the identity development of the secondgeneration Chinese American. Their different psychological conditions create a gap in their relationship and bring them to the crucial situation.To some extent, it is suggested for the next researcher to conduct a study by comparing The Joy Luck Club with other novels which are also written by Amy Tan. By using the comparative study, hopefully the next researcher can find out how Amy Tan builds the conflicts based on the psychological conditions of the characters in her novels.